IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAHAN PADA PELAPORAN KEUANGAN DAERAH (Studi pada Dinas Bina Marga Kabupaten Malang) - Pratiwi, Amelia Ika; Dwi Ardilatri, Rike Lulut (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
The Government Regulation No. 71 in 2010 has explained about the important information of how to write financial statement and how to present this statement in proper way. The objective of research is to understand and to analyze the presentation of financial statement made by Local Officer Work Unit (SKPD) of Bina Marga Official for Malang District based on the prevailed standard.Research type is quantitative descriptive. Data type includes qualitative and quantitative. Data source involves primary and secondary data. Data collection techniques are open observation, interview and literature study.Result of research has indicated that in 2013, Bina Marga Official for Malang District has presented financial statement in pursuance of Government Regulation No. 71 of 2010 and prepared it on time.Â Â  Keywords: Government Regulation No. 71 of 2010, Financial Statement, SKPD